Derrida for architects - Coyne, Richard (London ; New York : Routledge, 2011)
Prologue -- Thinking about architecture -- Language and architecture -- Intertextuality and metaphor -- Derrida on architecture -- Other spaces -- Derrida and radical practice
Bibliyografya ve dizin (sayfa 101-115) içerir.
Keywords: Architecture -- Philosophy; Mimarlık -- Felsefe